Design and Implementation of Sigma Delta Modulators (ΣΔM) for Class D Audio Amplifiers using Differential Pairs - Pereira, Nuno (Springer, 2015)
This book focuses on the design of a 3rd Order CT-ΣΔM where the integrator stages of the filter are implemented with Bipolar-Junction Transistors (BJT) differential pairs. These circuits are fully analyzed and the design method is carefully explained. The design method is validated through experimental measurements of several prototype circuits.